Informal Institutions in Azerbaijan: Exploring the Intricacies of Tapsh. Issue 4 (21st April 2017) - Aliyev, Huseyn
Abstract: Research on informal aspects of the post-communist economy and political institutions has developed rapidly since the collapse of the Soviet Union. While there is no lack in research on informal practices in Russia and other Eastern European countries, comprehensive empirical investigations of informality in peripheral regions of the former Soviet Union—such as the Caucasus and Central Asia—are still rare. This article aims to fill this gap by providing an evidence-based empirical account of informal practices in post-Soviet Azerbaijan. Drawing its empirical data from a two-decade-long ethnographic participant observation carried out in various locales of Azerbaijan's capital, Baku, this study offers nuanced insights into the hitherto unexplored informal practice of tapsh .